Auditor Choices in Family Companies - Hasni Yusrianti; Tertiarto Wahyudi; Aryanto Aryanto (Faculty of Economics, Universitas Sriwijaya, 2023)
This study aims to empirically examine the comparison of auditor choice and audit fees in family firms, as well as to test more comprehensively how the characteristics of family firms will influence the choice of auditors and audit fees in family firms. The purposive sampling results of this study show that the number of sample companies in this study is 133 non-financial companies listed on the Indonesia Stock Exchange in 2015-2021, with a total of 931 observations. The results of the logistic regression analysis of the auditor's choice model in this study indicate that family firms tend to be less choosing a high-quality auditor (auditor of KAP BIG4) and the presence of a CEO who is descended from the founder's family company is negatively related to the appointment of an auditor for KAP BIG4. In addition, the percentage of family ownership, the presence of the founder CEO of the family company and the presence of a professional CEO of the family company are not related to the appointment of KAP BIG4 auditors. The results of ordinary least square regression analysis using the robust standard error estimation method on the audit fee model show that family firms and the percentage of family members in top management are negatively related to audit fees, while the percentage of family ownership and the percentage of family members on the board of commissioners is not related to audit fees.